Benzimidazole resistance in a field population of Haemonchus contortus from sheep in Kenya - WARUIRU, R M (The Indian Journal of Animal Sciences, 2013)
A controlled anthelmintic efficacy test was used to confirm results of faecal egg count reduction test obtained earlier from a field survey where field strains of Haemonchus contortus were suspected to be resitant to thiabendazole (TBZ), fenbendazole (FBZ) and levamisole (LEV). Worm-free sheep (32) were experimentally infected with 2 strains of II.contortus (M1-3) and 3 anthelmintics were tested. There was 85 and 43% reduction, as compared with controls, in mean worm burdens (MWA) of sheep infected with M1 strain and killed 5 days after treatment with TBZ and FBZ, confirming their resistance to these anthelmintic. TBZ had an efficacy of 98% in sheep infected with M2 strain hut FBZ reduced MWB of the same strain in 10% indicating a moderate level of resistance to This anthelmintic. There was a 96% reduction in MWB of sheep infected with the suspected LEV -resistant M3 strain and then treated with LEV, indicating thai this strain was not resistant to LEV. There is a need to determine the anthelmintic efficacies of a gastrointestinal nematode population in any investigation on fa om where chemotherapeutic control measures against helminthiasis appear to have failed.